Community Perceptions Regarding the Utilization of Infrastructure Funds in Panggangsari Village, Cirebon Regency - Alfarikh Imam Fahrezi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
The existence of village funds raises new hope for rural communities. The funds originating from the APBN are programs that have the aim of prospering rural communities. Panggangsari Village receives a village fund budget and it always increases every year, but the increase is not in line with the surrounding environmental conditions, such as many roads with potholes indicating that village funds have not yet had an impact on the community. This study aims to determine how the community's perception of the utilization of village funds in Panggangsari Village, Cirebon Regency. This study used descriptive qualitative method. Data collection is sourced from primary data and secondary data. Data collection techniques used are in-depth interviews, observation, and literature study. The government's attention to the surrounding community is considered quite good because it involves residents in the preparation of the program, from the interested parties the government has placed the programs that are considered the most important to be prioritized, the habit of the surrounding community only knowing village funds from one another without knowing themselves, this causes the emergence of the community's negative stigma towards the government in using village funds, village communities tend to assess performance appraisals instantly without first looking for them.Keywords: Village Fund, Community Perception, Local Government.